2001
DOI: 10.1063/1.1358847
|View full text |Cite|
|
Sign up to set email alerts
|

Ferroelectric and electromechanical properties of poly(vinylidene-fluoride–trifluoroethylene–chlorotrifluoroethylene) terpolymer

Abstract: This letter reports the ferroelectric and electromechanical properties of a class of ferroelectric polymer, poly(vinylidene-fluoride–trifluoroethylene–chlorotrifluoroethylene) terpolymer, which exhibits a slim polarization hysteresis loop and a high electrostrictive strain at room temperature. The dielectric and polarization behaviors of this terpolymer are typical of the ferroelectric relaxor. The x-ray and Fourier transform infrared results reveal that the random incorporation of bulky chlorotrifluoroethylen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
195
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(201 citation statements)
references
References 13 publications
5
195
1
Order By: Relevance
“…The introduction of defect modifications to PVDF backbone can generate copolymers that exhibit certain advantages compared to homopolymer such as enhanced piezoelectric properties and improved mechanical behavior [26][27][28][29]. PVDF based materials are considered ideal candidates for several applications varying from electroacoustic and electromechanical convertors, actuators, ferroelectric memory devices to mechatronics and artificial muscles.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of defect modifications to PVDF backbone can generate copolymers that exhibit certain advantages compared to homopolymer such as enhanced piezoelectric properties and improved mechanical behavior [26][27][28][29]. PVDF based materials are considered ideal candidates for several applications varying from electroacoustic and electromechanical convertors, actuators, ferroelectric memory devices to mechatronics and artificial muscles.…”
Section: Introductionmentioning
confidence: 99%
“…As the bulky and less polar termonomer CTFE is randomly introduced into P(VDF-TrFE) normal ferroelectric crystals, there are three main features in the dielectric data of the polymer due to the addition of CTFE observed: (1) the original FP transition peak of the copolymer is moved to room temperature; (2) the peak becomes much broader and its position shifts progressively with frequency towards higher temperature; (3) there is no thermal hysteresis in the dielectric data, i.e., the broad dielectric peak stays at the same temperature when measured in the heating and cooling cycles. They also measured the polarization hysteresis loops at room temperature and -40°C 9 . The terpolymer exhibits a slim polarization loop at room temperature, and as the temperature is lowered, the coercive field increases and the polarization at maximum electric field decrease.…”
Section: Terpolymer P(vdf-trfe-ctfe)mentioning
confidence: 99%
“…Xu et al synthesized and evaluated terpolymer P(VDF-TrFE-CTFE) using the bulk polymerization method 9 . As the bulky and less polar termonomer CTFE is randomly introduced into P(VDF-TrFE) normal ferroelectric crystals, there are three main features in the dielectric data of the polymer due to the addition of CTFE observed: (1) the original FP transition peak of the copolymer is moved to room temperature; (2) the peak becomes much broader and its position shifts progressively with frequency towards higher temperature; (3) there is no thermal hysteresis in the dielectric data, i.e., the broad dielectric peak stays at the same temperature when measured in the heating and cooling cycles.…”
Section: Terpolymer P(vdf-trfe-ctfe)mentioning
confidence: 99%
“…However, recently it was found that the secondary chlorines in chlorotrifluoroethylene (CTFE) units of fluoropolymers are able to initiate ATRP of various monomers. [33] In this work, P(VDF-CTFE-TrFE), which exhibits relatively high performance among the PVDF-based polymers, [19,20] was chosen as the matrix material to synthesize the graft copolymer via single-step reaction. The mesogenic monomer, i.e.…”
Section: Characterizationmentioning
confidence: 99%
“…Among these crystalline phases, the polar β-phase is the most interesting and important one because it exhibits a strong ferroelectric behavior. [10][11][12] In order to obtain high performance and inexpensive electroactive polymers (EAPs), many efforts have been made to modify the crystal structure and morphology in the PVDF-based polymers, including studies of the effects of irradiation on PVDF-based copolymer [13][14][15][16] and terpolymers, [17][18][19][20] PVDF-based composites, [4,[21][22][23] and PVDFbased polymer blends with thermal treatment. [24][25][26] However, as an important method of modifying polymers, graft copolymerization of comonomers from the backbone of these ferroelectric fluoropolymers was seldom adopted to prepare high performance EAPs.…”
Section: Introductionmentioning
confidence: 99%